A study analyzing the clinical, histopathological and immunological profile of patients with cutaneous vasculitis: IgA vasculitis and non-IgA vasculitis - Kakroo, Shafia Nisar; Khan , Mohammad Ashraf; Beg, Mirza Aumir; Kakroo, Basit (Journal of Pakistan Association of Dermatologists, 2023)
Background: Vasculitis refers to an inflammatory process in the blood vessel wall. It is a spectrum of different diseases often associated with destruction of the vessel wall and occlusion of the vascular lumen. Since any vessel in any organ can be affected, clinical manifestations can vary widely. It comprises of a diverse group of disorders that combine segmental inflammation with necrosis of blood vessels. Immunoglobulins and complement components found in the blood vessel walls point towards the significance of antigen-antibody complexes in the pathogenesis of lesions. Vasculitis may be either limited to skin or manifest in other organ systems or both. In skin, it predominantly involves the venules and is known as Cutaneous Small Vessel Vasculitis (CSVV) or Leukocytoclastic vasculitis (LCCV). CSVV is clinically manifested by a spectrum of cutaneous lesions ranging from erythema and urticaria to ulcers and infarction, but palpable purpura is the hallmark of the disease. The diagnostic histopathological criteria of vasculitis includes swelling of endothelial cells, cellular infiltrate, fibrinoid necrosis in the vessel wall and in the perivascular zone and leukocytoclasia i.e, presence of nuclear dust within necrotic areas of vessel walls. Hence the leukocytoclastic vasculitis is appropriately used as a histopathological description than as a clinical entity. AIMS & OBJECTIVES: >To compare the demographic characteristics and clinical profile of patients with IgA vasculitis with that of non-IgA vasculitis. > To compare the systemic manifestations in these two groups with Special reference to renal involvement. Methods: Seventy five patients presenting to the outpatient clinic of a tertiary care hospital with a clinical diagnosis of palpable purpura were enrolled in the study . Detailed history and clinical examination is done in all patients and findings are recorded in a pre-designed proforma. Results: In IgA vasculitis, seventeen patients (42.5%) had vessel wall fibrin deposition & necrosis, sixteen (40%) patients had Inflammatory infiltration into vessel wall, fifteen patients (37.5%) had erythrocyte extravasation, eleven (27.5%) patients had nuclear dust and only nine patients (22.5%) had endothelial swelling. In IgA negative vasculitis five patients (14.28%) had vessel wall fibrin deposition & necrosis, ten patients (28.57%) had inflammatory infiltration into vessel wall, five patients (14.28%) had erythrocyte extravasation, and eleven patients (31.42%) had nuclear dust. Conclusion: In this study, we studied 75 patients of cutaneous vasculitis attending skin OPD. C3 was the commonest immunoreactant staining the blood vessel wall followed by FB and IgA. IgA vasculitis was seen in relatively younger age group compared to IgA negative vasculitis.